Diabetes Mellitus and Clinical Outcomes in Carotid Artery Revascularization Using Second-Generation, MicroNet-Covered Stents: Analysis from the PARADIGM Study. (26th September 2022) - Mazurek, Adam; Borratynska, Anna; Gancarczyk, Urszula; Czyz, Lukasz; Sikorska, Martyna; Tekieli, Lukasz; Sobien, Bartosz; Jakiel, Marcin; Trystula, Mariusz; Drazkiewicz, Tomasz; Podolec, Piotr; Musialek, Piotr
Abstract : Introduction . Carotid artery stenting (CAS) using conventional (single-layer) stents is associated with worse clinical outcomes in diabetes mellitus (DM) vs. non-DM patients: an effect driven largely by lesion-related adverse events. CAS outcomes with MicroNet-covered stents (MCS) in diabetic patients have not been evaluated. Aim . To compare short- and long-term clinical outcomes and restenosis rate in DM vs. non-DM patients with carotid stenosis treated using MCS. Materials and Methods . In a prospective study in all-comer symptomatic and increased-stroke-risk asymptomatic carotid stenosis, 101 consecutive patients (age 51-86 years, 41% diabetics) underwent 106 MCS-CAS. Clinical outcomes and duplex ultrasound velocities were assessed periprocedurally and at 30 days/12 months. Results. Baseline characteristics of DM vs. non-DM patients were similar except for a higher prevalence of recent cerebral symptoms in DM. Type 1 and type 1+2 plaques were more prevalent in DM patients (26.7% vs. 9.8%, p = 0.02 ; 62.2% vs. 37.7%, p = 0.01 ). Proximal embolic protection was more prevalent in DM (60% vs. 36%; p = 0.015 ). 30-day clinical complications were limited to a single periprocedural minor stroke in DM (2.4% vs. 0%, p = 0.22 ). 12-month in-stent velocities and clinical outcomes were not different (death rate 4.8% vs. 3.3%; p = 0.69 ; no new strokes). Restenosis rate was not different (0% vs. 1.7%, p = 0.22 ). Conclusions. MCS may offset the adverse impact of DM on periprocedural, 30-day, and 12-month clinical complications of CAS and minimize the risk of in-stent restenosis. In this increased-stroke-risk cohort, adverse event rate was low both in DM and non-DM. Further larger-scale clinical datasets including extended follow-ups are warranted.